Agriculture 2 in 1 Assisting Machine - Yunus, Nurul Afiq; Abd Kahar, Hartiny; Naim, Muhammad Akid (Multidisciplinary Applied Research and Innovation, 2021)
Crop farmers use manual agricultural tools in farming or other agriculture-related activities such as break up and loosening hard, compact soil, crop boundary-making, fertilizing, pest/weeds control, which consumed much time and energy for them. The objectives of Agriculture 2 In 1 Assisting Machine are to facilitate the crop farmer’s work in the early stages such as loosening the soil and boundaries making for the crop planting, also for fertilizing/pests and weeds control by combining different functions in 1 machine. The methodology of this design includes metal joining - welding for fabrication, electrical installation for spraying system and the power source connection for rechargeable batteries combined with solar panels as an environmentally friendly power alternative. In conclusion, the machine is able to loosen the soil and forming the boundaries simultaneously and to be used in fertilizing/pest control using a solar-powered battery. This will reduce time consumed, minimize human power and increase efficiency.